The acceptability of overdose alert and response technologies: introducing the TPOM-ODART framework - Josh Dumbrell; Hadi Daneshvar; Alberto Oteo; Alexander Baldacchino; Catriona Matheson (BMC, 2023)
Abstract Background Opioids were implicated in approximately 88,000 fatal overdoses (OD) globally. However, in principle all opioid OD are reversible with the timely administration of naloxone hydrochloride. Despite the widespread availability of naloxone among people who use opioids (PWUO), many who suffer fatal OD use alone, without others present to administer the reversal agent. Recognising this key aspect of the challenge calls for innovations, a number of technological approaches have emerged which aim to connect OD victims with naloxone. However, the acceptability of OD response technologies to PWUO is of key concern. Methods Drawing on the Technology People Organisations Macroenvironment (TPOM) framework, this study sought to integrate acceptability-related findings in this space with primary research data from PWUO, affected family members and service providers to understand the factors involved in harm reduction technology acceptability. A qualitative study using a focus group methodology was conducted. The participant groups were people with lived experience of problem opioid use, affected family members and service providers. Data analysis followed a multi-stage approach to thematic analysis and utilised both inductive and deductive methods. Results Thirty individuals participated in one of six focus groups between November 2021 and September 2022. The analysis generated six major themes, three of which are reported in this article-selected for their close relevance to PWUO and their importance to developers of digital technologies for this group. 'Trust-in technologies, systems and people' was a major theme and was closely linked to data security, privacy and confidentiality. 'Balancing harm reduction, safety and ambivalence' reflects the delicate balance technological solutions must achieve to be acceptable to PWUO. Lastly, 'readiness-a double bind' encapsulates the perception shared across participant groups, that those at the highest risk, may be the least able to engage with interventions. Conclusion Effective digital strategies to prevent fatal OD must be sensitive to the complex relationships between technological, social/human, organisational and wider macroenvironmental factors which can enable or impede intervention delivery. Trust, readiness and performance are central to technology acceptability for PWUO. An augmented TPOM was developed (the TPOM-ODART).